Estrategia psicopedagógica para superar las dificultades de la comprensión lectora en estudiantes de sexto grado de educación básica paralelo a, de la unidad educativa Adolfo Valarezo, 2019-2020. - Andrade Quizhpe, Anghelo David (2021)
This research is entitled: PSYCHO-PEDAGOGICAL STRATEGY FOR OVERCOMING THE DIFFICULTIES OF READING COMPREHENSION IN STUDENTS IN THE SIXTH GRADE PARALLEL A, BASIC EDUCATION FROM THE ADOLFO VALAREZO EDUCATIONAL UNIT, 2019-2020, the general objective was to propose a Psychopedagogical strategy to overcome the difficulties of reading comprehension. This descriptive explanatory research; nonexperimental cross-sectional design; the following scientific, analytical, inductive, and deductive methods were used; the Reader Process Evaluation Battery (PROLEC-R) was applied to the sample of 24 students from “Adolfo Valarezo” educational unit. Regarding the most relevant results, it was found that: Table 2: test 1; identification of letter, 50% have slight difficulties in the activity name of letters; Table 3: test 2: lexical processes, 70, 83% showed severe difficulties in the activity Reading words; Table 4: test 3: syntactic processes 91, 67% show severe difficulty in punctuation marks activity of understanding sentences; Table 5: test 4: semantic processes, 95, 83% show severe difficulties in the activity of understanding sentences. It is concluded that those investigated have mild and severe difficulties in certain activities processes of reading comprehension. It was concluded that the students present difficulties in reading comprehension, being located in levels of mild and severe difficulty.